2000
DOI: 10.1080/000163500429226
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine cells in Malassez epithelium and gingiva of the cat

Abstract: Malassez epithelium has been designated as epithelial cell rests, the biological significance of which is still under debate. This study was designed to analyze Malassez epithelium for the presence of neuroendocrine cells. Gingival tissue was included as a positive control. Using immunohistochemistry, confocal and light microscopy, Malassez epithelium and gingival epithelium from mature cats (n = 5) were examined for cells containing the neuropeptides calcitonin gene-related peptide (CGRP), substance P (SP), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…Immunohistochemical and immunoelectron microscopic analyses have verified the presence and colocalization of several neuropeptides in single cells of ERM clusters (Kvinnsland et al, 2000;Tadokoro et al, 2002Tadokoro et al, , 2003. In addition to neuroendocrine cells, immunocompetent cells have also been confirmed in the vicinity of the ERM in rat PDL induced by mechanical, orthodontic force (Vandevska-Radunovic et al, 1997).…”
mentioning
confidence: 77%
“…Immunohistochemical and immunoelectron microscopic analyses have verified the presence and colocalization of several neuropeptides in single cells of ERM clusters (Kvinnsland et al, 2000;Tadokoro et al, 2002Tadokoro et al, , 2003. In addition to neuroendocrine cells, immunocompetent cells have also been confirmed in the vicinity of the ERM in rat PDL induced by mechanical, orthodontic force (Vandevska-Radunovic et al, 1997).…”
mentioning
confidence: 77%
“…It has recently been reported that ERM express hard-tissue-related proteins such as enamel and bone morphogenetic proteins during cementum repair (Hasegawa et al 2003). It has also been demonstrated that periodontal nerve endings and ERM have a close relationship (Lambrichts et al 1993;Kvinnsland et al 2000;Tadokoro et al 2002Tadokoro et al ,2003 and that an interaction between PDLderived epithelial cells and fibroblasts regulates the expression of alkaline phosphatase, osteocalcin, and bone sialoprotein (Shimonishi et al 2005(Shimonishi et al ,2008. These reports suggest that ERM function not independently, but through interaction with other cells or in response to extrinsic stimuli.…”
mentioning
confidence: 99%
“…The present study showed that the epithelial layer of Malassez seemingly divides areas rich in innervation from areas with only sparse innervation. Kvinnsland et al [19] found neuro-endocrine cells in the Malassez epithelium in the rat. In the present study, it was difficult to locate nerve fibers specifically in the epithelial layer of Malassez.…”
Section: Discussionmentioning
confidence: 98%